The global economic crisis from a sociological perspective: civilisational roots, individual and social repercussions - Leonarska, Dorota; Wielecki, Krzysztof (Economy Today: An Interdisciplinary Approach to Contemporary Economic Challenges, 2016)
This article is an attempt of a sociological reflection on economics and the latest global economic crisis. The authors focus on the social and individual impacts of the economic crisis, because global economic processes directly influence and severely touch individual human beings. Its repercussions can be observed not only at the economic level, but also analysed in a sociological and psychological sense.The purpose of this article is to explore the implications of the economic crisis at the social level. The economic crisis is synonymous with the crisis of capitalism, which is only an aspect of a much wider and more serious civilisational crisis of our time. The economy should be understood in the context of the social order – being only one of its five aspects or dimensions – it is influenced by and in turn influences the remaining aspects of the social order. This article is based on statistical analysis, comparative research on chosen European countries, as well as a critical reflection on international sociological literature in this domain.It provides a comparative sociological analysis of two ideal types (in a Weberian sense), two different orientations clearly emerging in the contemporary economy- unconditioned, ruthless capitalism on one side, and a more pro-social capitalism on the other. These trends are the subject of analysis and debate in sociological literature. Each orientation has very different implications at the social level, creating societies with different social values and diverse levels of cultural and social capital.